A multifuncionalidade das paisagens rurais : uma ferramenta para o desenvolvimento - Galvão, Maria João (2010)
Throughout the last years, the rural landscape has been severely altered. Agriculture always played an important role in establishing the dynamics of the landscape, allowing it to contribute to its "construction". Nowadays, agriculture has become just one of the activities of the rural world. In Europe, it has been reinforced the multifunctional character of rural landscapes, especially in what concerns agriculture. When we speak about multifunctionality in agriculture, we are considering that the agricultural activity comprises other functions other than the production of agricultural and agro-industry goods. This activity is not just directed at the pure competitiveness of the production but rather plays an essential role for the development of rural areas by preserving, for instance, the culture and traditions of the people. The Council of Figueira de Castelo Rodrigo is predominantly a rural territory. In the last few decades it has been facing some of the problems that characterize most of the Portuguese interior regions. Beginning at the biophysical and human characteristics of this Council, a new proposal for resource planning and development was established, having in mind the concept of spaces multi-functionality.